Associations between functional movement screen scores and performance variables in surf athletes - Silva, B.; Clemente, F. M.; Martins, F. M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Functional movement screen (FMS) have been used to assess the movement patterns in daily sports practice. Some associations between FMS scores and physical variables have been found in some sports. Nevertheless, no study was conducted in surf. METHODS: Eighteen surf athletes (11 male) participated in the study (18.3±6.3 years; 60.0±9.6 kg; 168.6±8.1 cm). All participants completed anthropometrics, knee-to-wall test, Functional Movement Screen, Isometric Knee Extension, Handgrip, Squat and Countermovement Jump. Based on that, this study investigated: 1) the variance of FMS scores between gender; 2) the association between FMS scores and physical variables of strength of upper and lower limbs, power of lower limbs and anthropometric variables; and 3) which FMS scores best explain the physical performance variables. RESULTS: The analysis of comparison between gender of each item of FMS showed significant statistical differences only in trunk stability push-up (P=0.01, ES=0.141). Kendall`s Tau b correlation test between FMS scores and physical variables, revealed significant associations. After performed the stepwise multiple linear regression, FMS deep squat and trunk stability push-up explain 57% of right side knee-to-wall test and the model is statistically significant (F(2,15)=13.097; P=0.001). In squat jump (height) the results show that FMS trunk stability push-up explains 50.3% of this dimension and the model is statistically significant (F(1,16)=18.182; P=0.001). CONCLUSIONS: FMS individual scores seems to better explain physical variables than total score. Only trunk stability push-up test seems to be a reliable indicator to predict physical performance in surf athletes.